ANALISIS FERITIN DAN AST TO PLATELET RATIO INDEX SEBAGAI PETANDA DERAJAT FIBROSIS PENYAKIT HATI KRONIS (Analysis Ferritin and AST to Platelet Ratio Index as a Marker Degree of Fibrosis Chronic Liver Disease) - Yulianti Yasin; Uleng Bahrun; Ibrahim Abdul Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Chronic liver disease is an endemic disease in Indonesia which is still a global health problem and detected when it’s developinginto fibrosis. The determination of fibrosis is important for the treatment and prognosis of chronic liver disease. AST to Platelet RatioIndex (APRI) score is the most common used to assess the degree of liver fibrosis. Ferritin is an iron deposit that found in the liver andthe levels depend on the degree of the cell damage. The aim of this study was to analyze ferritin levels as a marker of the fibrosis degreein the chronic liver disease. This cross-sectional study of 47 patients with chronic liver disease performed at Dr. Wahidin SudirohusodoGeneral Hospital between May–June 2012. The subjects are grouped into cirrhotic and noncirrhotic, based on the theory that in cirrhoticliver fibrosis was considered as an irreversible condition. AST to platelet ratio index score based on the Wai CT formulation, includingthe examination of AST by optimizing UV-test according to International Federation of Clinical Chemistry (IFCC) modified method onthe ABX Pentra 400, examination of platelet by impedance method on Sysmex XT 2000i and ferritin levels were measured by ECLIAmethod using Elecsys 2010 Analyzer. The Spearman correlation tests showed no association between ferritin levels and APRI in cirrhoticand non cirrhotic patients (p=0.704 and r=–0.057). In conclusion, ferritin can not be used as the marker in determining the degreeof fibrosis patients suffering chronic liver disease. Further studies are expected using a more valid method for determining the degree offibrosis such as liver biopsy or fibro scan.